Performance of Amino Acid Supplementation in Feed on the Production of Cantang Grouper (Epinephelus lanceolatus x Epinephelus fuscoguttatus) in the Nursery Phase - Rahardjo, Seto Sugianto Prabowo; Kurniawan, Hendra Agung; Oktaviani, Elsa Dian; Wibawa, Gigih Setia; Widyawati, Yuni; Mahariawan, I Made Dedi (Universitas Teuku Umar, 2024)
The growth of Cantang grouper is influenced not only by genetic factors but also by the quality of feed, particularly the protein content, which is closely related to amino acid levels. This study aims to investigate the effect of adding commercial amino acids to feed on the growth of Cantang grouper. The research was conducted using an experimental method with a Randomized Block Design (RBD), comprising four treatments and three replicates of amino acid doses added to commercial feed: P0 (0%), P1 (1%), P2 (2%), and P3 (3%). The parameters observed included survival rate, weight growth rate, length growth rate, specific growth rate, and feed conversion ratio. The results showed that adding amino acids to commercial feed over a 21-day rearing period significantly affected all parameters (p<0.05). The highest survival rate, weight growth, length increase, and specific growth rate were found in the P2 treatment with the values of 95.00 ± 5.00%, 7.40 ± 0.24 g, 3.69 ± 0.75 cm, 9.83 ± 0.15%/day, respectively. In addition, the lowest feed conversion ratio was obtained in the P2 treatment (1.22 ± 0.03).